Perancangan Grafis sebagai Penciptaan Nilai untuk Kemasan Ayam Goreng Basah - Zulkarnain Zulkarnain; Helpy Agriffina Syom; Tajuddin Bantacut (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
The packaging function has evolved into a brand value creation tools to customers. "Ayam Goreng Basah" is a food product from catering service by Ibu Siti Sugiyanti that uses packing box and styrofoam without any graphic design on the packaging, which can be a communication tool to the customers. The purpose of this study is to apply the graphics design process of “Ayam Goreng Basah” package. This research was conducted by collecting information from customers through brainstorming. The brainstorming activities have made a creative idea concept "Inovasi Ayam Goreng Nusantara", which became a base in visualizing the packaging graphic of Ayam Goreng Basah. Graphic design that received the highest score at the RIII (Bumbu Rempah-Rempah Khas Nusantara) with a total score (8:35).Keywords: Graphic Process, Brainstorming, Graphic Design Packaging.